SULFATE-CONTAINING CEMENTS BASED ON PHOSPHOGYPSUM AND OTHER MATERIALS (Academia Science Repository, 2023)
The use of phosphogypsum in an amount of 6 to 49 in the composition of raw materials made it possible to obtain clinker of various mineralogical composition, by adjusting which, depending on the need, it is possible to produce non-shrinking, high-strength, expanding and stressing cements of various grades.